1997
DOI: 10.1177/000765039703600302
|View full text |Cite
|
Sign up to set email alerts
|

Socially Irresponsible and Illegal Behavior and Shareholder Wealth

Abstract: This article provides empirical results indicating that acting in a socially respon- sible and lawful manner is a necessary, though not sufficient, condition for increasing shareholder wealth. It meta-analyzes 27 event studies that have mea- sured the stock market's reaction to incidences of socially irresponsible and illicit behavior. It finds that for firms engaging in socially irresponsible and illicit behavior, the effect on shareholder wealth is negative (wealth decreases), statisti- cally significant (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
248
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(264 citation statements)
references
References 44 publications
7
248
0
9
Order By: Relevance
“…When customers are dissatisfied with a product or its associated services, investors apprehend that negative customer reactions in the form of decreased patronage, lawsuits, or both, will directly affect the bottom line (Berman et al, 1999). Event studies establish that market value of a company decreases when corporate irresponsibility and illegal behavior is observed (Frooman, 1997). The news of pesticide content in Pepsi and Coca-Cola beverages in India reduced the sales of both companies by 60% (Financial Express, 2006).…”
Section: Csr Towards Customers and Firm Performancementioning
confidence: 99%
“…When customers are dissatisfied with a product or its associated services, investors apprehend that negative customer reactions in the form of decreased patronage, lawsuits, or both, will directly affect the bottom line (Berman et al, 1999). Event studies establish that market value of a company decreases when corporate irresponsibility and illegal behavior is observed (Frooman, 1997). The news of pesticide content in Pepsi and Coca-Cola beverages in India reduced the sales of both companies by 60% (Financial Express, 2006).…”
Section: Csr Towards Customers and Firm Performancementioning
confidence: 99%
“…CSR also reduces business risk (Moore, 2001;Orlitzky & Benjamin, 2001). Certain event studiesalso prove that CSR increase the profitability (Frooman, 1997). Therefore, it can be conjectured from literature that CSR leads to better corporate financial performance of firms.…”
Section: Csr and Financial Performancementioning
confidence: 99%
“…: Despite this, research, bibliometric analyses (De Bakker et al 2005) and recent meta analyses have produced a common stand which tends to overcome these problems (Allouche and Laroche 2005;Orlitzky et al 2003;Orlitzky and Benjamin 2001;Frooman 1997;Wu 2006;Margolis et al 2007), providing evidence of a positive correlation between CSR and economic performance. Margolis et al (2007) concluded, After 35 years of research, the preponderance of evidence indicates a mildly positive relationship between corporate social performance (CSP) and CFP'.…”
Section: The Business Case Of Csr: Csr and Its Relationship With Compmentioning
confidence: 99%